Investigation of the influence of the energy conditions of pulsed plasma-chemical synthesis on the morphological and structural properties of copper-containing silica-based nanocomposites - Ponomarev, Denis; Kholodnaya, Galina; Sazonov, Roman V.; Lapteva, Olga; Konusov, Fedor V.; Gadirov, Ruslan M. (International journal of materials research)
This paper presents the results of a study of the effect of energy conditions (additional heating of the walls of the reaction chamber and subsequent action of an electron beam on the synthesized powder) of pulsed plasma-chemical synthesis on the morphology, average geometric size, phase and chemical composition of copper-containing silica-based nanocomposites. The nanocomposites were synthesized using a TEA-500 pulsed electron accelerator. It was the first time that copper-containing silica-based nanocomposites had been prepared using the pulsed plasma-chemical synthesis. The values of the band gap for the as-prepared nanocomposites were calculated. The nanocomposites were characterized by means of transmission electron microscopy and X-ray diffraction. The analysis revealed the changes in the morphology and phase composition of the nanocomposites upon energy conditions.